INTEGRASI KEILMUAN UMUM DAN AGAMA - Rijal, Syamsul (Universitas Islam Madura, 2017)
General science (science) growing rapidly while the decline of Islamic science, which in the end came the dichotomy between the two disciplines. Not only here but there are also the secularization of science. But secularization of science has been challenged by the Church. Awarding a penalty to the scientists who dare to be different views with the Church to trigger the birth of science that separates itself from religious doctrine. This condition motivates Muslim scholars try hard to re-integrate science and religion. Thinking about integration or the Islamization of science today is carried out by Muslim intellectuals, can not be separated from religious awareness. In totality amid hectic global world that is loaded with the progress of science and technology. Real science is the result of a human reading the verses of Allah, losing the dimension of spirituality, then berkembangkanlah science or science that has no connection with religion. It is not surprising then that the science and technology that should benefit as much as possible for human life turned out to be a tool used for temporary interest that it be a